Application of muscle rub on overall physical performance in athletes - Chiam, Melody Jiale (Nanyang Technological University, 2020)
Introduction: Muscle rubs have been marketed as a replacement for warm-up. The author’s objective was to understand whether muscle rub application would improve overall physical performance and possibly be implemented into athletes’ pre-workout if significant results are rendered. Methods: The experimental design was single-blinded, involving twenty athletes from Nanyang Technological University (NTU), who were randomized evenly by gender to either receive the muscle rub or placebo. The dependent variables were, Deep Squat (DS) rating, Sit-and-Reach scores, normalized Y-Balance distance, and Standing Broad Jump (SBJ) distance. Results: Although from pre-test to post-test, the muscle rub group showed improvements in scores, results indicated that the interaction effect was statistically non-significant (p > 0.05) in all test components. However, when compared between genders, there were significant differences (p < 0.05) in scores in Sit-and-Reach and SBJ components. Discussion and Conclusion: This study suggests that muscle rub application on lower limbs had no superior effect to placebo application and no improvement in performance was rendered.